Effect of tillage and soil amendments on soil quality and yield of clusterbean (Cyamopsis tetragonoloba) in shallow hardpan soils of arid Gujarat - MANGALASSERY, S; DAYAL, DEVI; RAM, B; MEENA, S L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at CAZRI, Regional Research Station, Kukma-Bhuj during kharif 2009 to find out the management options for improving soil productivity and quality in shallow hard pan soils in arid Gujarat. There were four tillage treatments, viz no-tillage, minimum tillage, shallow tillage and deep tillage in main plots and four amendments (gypsum at 5 Mg/ha, farmyard manure (FYM) at 5 Mg/ha and both gypsum and FYM at 5 Mg/ha each and control) in sub plots. The results of the experiment showed that deep tillage along with the application of gypsum and FYM at 5 Mg/ha produced maximum yield and maximum net returns. The study found a decreased yield and negative net returns under no-tillage in these shallow hard pan soils. However soil biological and physical properties were better under no-tillage. Long term studies may be necessary to find out the applicability of no-tillage in these soils from a yield perspective.